Constitutive behavior and fracture of intermetallic compound layer in bimetallic composite materials: Modeling and application to bimetal forming process. (15th December 2021) - Rajhi, Wajdi; Ayadi, Badreddine; Khaliq, Abdul; Al-Ghamdi, Abdulaziz; Ramadan, Mohamed; Al-shammrei, Shaher; Boulila, Atef; Aichouni, Mohamed
Graphical abstract: Highlights: A novel experimental-computational approach to characterize shear fracture behavior of IMC layer for bimetallic forming applications was established. Thermodynamic of irreversible processes and continuum damage mechanics (CDM) were used as frameworks for constitutive model of damaged IMC layer. A damage mechanism of quasi-brittle character was the cause of Al-Sn alloy/mild steel IMC fracture under tensile-shear loading. Delamination and intra-laminar cracks characterized the crack propagation behavior in U-bending of bimetal. Abstract: This paper presents a novel experimental and computational methodology to characterize the fracture behavior of the intermetallic bonding layer particularly for the bimetallic forming applications. The proposed methodology was applied to Al-Sn bearing alloy/mild steel bimetallic composite. Tensile-shear bimetal samples were fabricated to test the metallurgical bonding layer under shear conditions. Based on the macroscopic behavior, the coupled elasto-plasticity and damage constitutive equations for the bond material were formulated and implemented. The used damage model is written within the framework of the thermodynamic of irreversible processes with the concept of internal state variables and the framework of continuum damage mechanics (CDM). The characterization of the shear fracture behavior of the bond has included FE numerical simulation of tensile-shear tests of the bimetallic composite using ABAQUS/Explicit® FE code with the specially developed VUMAT subroutine. Accordingly, a calibration approach has been proposed to identify the fracture parameters of the bond based on the correspondence between the numerically predicted and experimental global shear force–displacement responses. These parameters have been applied to FE model of the U-bending testing of Al-Sn /mild steel bimetallic composite. A qualitative correspondence between numerically predicted results and U-bending experiment of the bimetal conducted under high-speed camera is deemed extremely satisfactory.